Expanded range of Nasutitermes callimorphus Mathews, 1977 (Isoptera: Termitidae: Nasutitermitinae), comparison with N. corniger (Motschulsky, 1855) and N. ephratae (Holmgren, 1910), and synonymy of N. dasyopsis Thorne, 1989 into N. nigriceps (Haldeman, 1854) - Scheffrahn, Rudolf H.; Roisin, Yves; Szalanski, Allen L.; Austin, James W.; Duquesne, Edouard (Zootaxa, 2024)
The imago of N. callimorphus is described for the first time. Nasutitermes callimorphus occurs from Mexico to Paraguay. Nasutitermes callimorphus is smaller in all measurements but generally resembles its widely distributed sympatric congeners, N. corniger (Motschulsky, 1855) and N. ephratae (Holmgren, 1910). Molecular phylogenetic analysis of a portion of the mitochondrial 16S rRNA gene and the COII mtDNA marker revealed that N. callimorphus forms a distinct clade using both maximum parsimony and maximum likelihood analysis. Unlike N. corniger and N. ephratae, N. callimorphus does not build epigeal or arboreal carton nests. We further regard N. dasyopsis Thorne, 1989 as a junior synonym of N. nigriceps (Haldeman, 1854).